Reversible Edema in the Penumbra Correlates With Severity of Hypoperfusion. Issue 7 (13th May 2021) - Scheldeman, Lauranne; Wouters, Anke; Dupont, Patrick; Christensen, Soren; Boutitie, Florent; Cheng, Bastian; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Gerloff, Christian; Muir, Keith W.; Nighoghossian, Norbert; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We aimed to investigate fluid-attenuated inversion recovery changes in the penumbra. Methods: We determined core and perfusion lesions in subjects from the WAKE-UP trial (Efficacy and Safety of MRI-Based Thrombolysis in Wake-Up Stroke) and AXIS 2 trial (Granulocyte Colony-Stimulating Factor in Patients With Acute Ischemic Stroke) with perfusion- and diffusion-weighted imaging at baseline. Only subjects with a mismatch volume >15 mL and ratio >1.2 were included. We created voxel-based relative fluid-attenuated inversion recovery signal intensity (rFLAIR SI) maps at baseline and follow-up. We studied rFLAIR SI in 2 regions of interest: baseline penumbra (baseline perfusion lesion−[core lesion+voxels with apparent diffusion coefficient <620 10 −6 mm 2 /s]) and noninfarcted penumbra (baseline perfusion lesion−follow-up fluid-attenuated inversion recovery lesion) at 24 hours (WAKE-UP) or 30 days (AXIS 2). We analyzed the association between rFLAIR SI and severity of hypoperfusion, defined as time to maximum of the residue function. Results: In the baseline penumbra, rFLAIR SI was elevated (ratio, 1.04; P =1.7×10 − 13 ; n=126) and correlated with severity of hypoperfusion (Pearson r, 0.03; P <1.0×10 − 4 ; n=126). In WAKE-UP, imaging at 24 hours revealed a further increase of rFLAIR SI in the noninfarcted penumbra (ratio, 1.05 at 24 hours versus 1.03 at baseline; P =7.1×10 −3 ; n=43). In AXIS 2, imaging at 30 days identified reversibility of the rFLAIR SI (ratio, 1.02 at 30 days versus 1.04 at baseline; P =1.5×10 −3 ; n=26) since it was no longer different from 1 (ratio, 1.01 at 30 days; P =0.099; n=26). Conclusions: Penumbral rFLAIR SI increases appear early after stroke onset, correlate with severity of hypoperfusion, further increase at 24 hours, and are reversible by 30 days. Registration: URL: https://clinicaltrials.gov ; Unique identifier: NCT01525290. URL: https://clinicaltrials.gov ; Unique identifier: NCT00927836.